Anchoring polydentate N/O-ligands in metal phosphite/phosphate/phosphonate (MPO) for functional hybrid materials - Han, Song-De; Hu, Ji-Xiang; Li, Jin-Hua; Wang, Guo-Ming (Coordination chemistry reviews, 2023)
This review summarizes the strategies towards anchoring polydentate N/O-ligands in metal phosphite/phosphate/phosphonate (MPO)-based supramolecular building blocks (SBBs) to generate hybrid MPO materials with novel functionality including photochromism, photomagnetism, and room temperature phosphorescence. The molecular design, assembly strategy, structure-functionality relationships and properties expansion are highlighted. [Display omitted] •Anchoring polydentate N/O-ligands in metal phosphite/phosphate/phosphonate (MPO) for functional hybrid materials has been reviewed.•Structures and structure-dependent functionalities of hybrid MPOs have been illustrated.•Further studies of hybrid MPOs based on polydentate N/O-ligands is suggested. The investigation of metal phosphates/phosphites (MPOs) has received continuous interest of researchers because of their diverse structural characteristics and interesting chemo-physical properties. Compared with inorganic phosphate/phosphite, organic phosphonate not only inherits the structural characteristics of inorganic phosphate/phosphite, but also shows tunable constituents, which provides extra freedom to yield novel hybrid materials with expanding application and broaden the research scope of traditional MPOs. Recent studies have demonstrated that the intermarriage of polydentate N/O-ligands and metal phosphites/phosphates/phosphonates (MPOs) gives birth to a new category of hybrid materials. The topic of this review is to propose strategies towards anchoring polydentate N/O-ligands in MPO-based supramolecular building blocks (SBBs) to generate functionalized MPO-based hybrid materials, reveal relationships between the microscopic functional struct-units and macroscopic physical functionality of resultant hybrid MPOs, extend the available functionality in the field of MPO-studies. Such a topic aims at enriching the research scope of MPOs from conventional MPOs (organically templated phosphates and phosphites with inorganic host structs) to unconventional MPOs (phosphates, phosphites and phosphonates decorated by polydentate N/O-ligands with hybrid host structs) in structural constituents, from traditional applications (adsorbent, ion-exchanger and catalyst) to emerging applications (room temperature phosphorescence (RTP), photochromism, photomagnetism, etc) in properties expansion. This review would offer valuable guidance for researchers engaged in MPO-based materials, and eventually facilitate the new studies of hybrid MPOs materials with desirable properties.